Estudo de códigos LDPC em sistemas OFDM com modulações 16-APSK sobre canal Rayleigh - Menezes Júnior, José Clair (2014)
In this master s thesis, a wireless communication scheme with a single transmit and single receive antenna, SISO case, with use of the OFDM multicarrier technique and application of LDPC coding was considered. It is well known that one of the biggest challenge related to OFDM system refers to the reduction of the peak-to-average power ratio (PAPR) factor. Thus this master s thesis proposes the use of 16-APSK and 16-QAM modulations by aiming to mitigate the PAPR factor. It is also considered the use of LDPC codes to evaluate the performance of bit error rate (BER) versus signal-to-noise ratio (SNR) performance for the 16-QAM, A16- QAM and 16-APSK constellations. The LDPC codes were adopted since they are one of the most effective methods of channel coding presented in the literature. Monte Carlo simulations were performed in AWGN and Rayleigh fading channels in order to evaluate the system performance in terms of BER × SNR and the PAPR factor analysis from the perspective of CCDF curves. Results reveal that with the use of LDPC codes associated with the use of 16-APSK constellations in multicarrier systems promotes BER performance gain and also reduction of the PAPR factor.